Peningkatan Kemampuan Sosial Anak Melalui Permainan Labirin di TK Thoyyibah Kota Sawahlunto - Eli Marlita, Desi (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The social abilities of children in group B of Thoyyibah Kindergarten have not yet fully developed well. This is one of the main reasons and incentives for conducting research. The aim of this research is to improve children's social skills through the Labyrinth game. This type of research is Classroom Action Research. There were 10 children in group B, namely 5 boys and 5 girls who were the research subjects. In this research, there are 2 cycles, namely cycle I and cycle II, where each cycle consists of 4 stages: planning, implementation, observation, and reflection. By using this maze game, it can improve the social skills of children in group B at Thoyyibah Kindergarten. The increase in children's social abilities in each cycle, which in cycle I was 32.5%, and increased in cycle II with the achievement criteria to 82.5%.